Von den Möglichkeiten translatorischen Handelns: Eine performative, ausgangskulturorientierte Perspektive am Beispiel Antoine Gallands und der ‚Tausend und eine Nacht‘ - Alhussein, Akkad (chronotopos – A Journal of Translation History, 2020)
This article deals with the translation history of the Arabic narratives of the ‘Thousand and One Nights’ from a performative, source culture-oriented perspective. The two-stage nature of the translation process as interlingual/bilingual communication implies a one-dimensional linearity that determines the relationship between source and target text. The effects of translation on the production/reception of the source text fall beyond the conceptual scope of the concept of translation and cannot, in principle, be dealt with in a translation-theoretical framework, resulting in a static-genetic conception of the source text as a “source”. I will use the 'Thousand and One Nights' to argue that a new concept of translation as a performative movement towards the source text can better demonstrate the complexity of translational action and expand the interpretative possibilities of translation as an interaction between a source text and a target text. The role of Antoine Galland and his translation of the ‘Thousand and One Nights’ (Les mille et une nuits) is highlighted.